2016
DOI: 10.1097/md.0000000000004957
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and endometriosis risk in women with infertility or pain

Abstract: Background:The potential association between endometriosis and physical activity (PA) has been suggested in several epidemiological studies.We aimed to establish whether PA influences endometriosis risk.Methods:MEDLINE and EMBASE were searched using “physical activity” OR “exercise” combined with “endometriosis,” in Medical Subject Headings and free text. We selected original articles in English, published up to April 2016, evaluating the association between endometriosis and recent or past PA (case–control or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 34 publications
0
42
0
5
Order By: Relevance
“…Adding to the previous , a case control study, related the risk of endometriosis to other less studied factors such as anthropometric variables (height, weight and BMI), physical exercise, smoking, and alcohol consumption. The authors observed an inverse association between [15], also pointed that is possible that the protective effect of exercise in patients with endometriosis result from the fact that women who suffer from endometriosis do not feel well enough to practice exercise. In general, curative treatment alone is not enough to promote health.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Adding to the previous , a case control study, related the risk of endometriosis to other less studied factors such as anthropometric variables (height, weight and BMI), physical exercise, smoking, and alcohol consumption. The authors observed an inverse association between [15], also pointed that is possible that the protective effect of exercise in patients with endometriosis result from the fact that women who suffer from endometriosis do not feel well enough to practice exercise. In general, curative treatment alone is not enough to promote health.…”
Section: Discussionmentioning
confidence: 86%
“…Also [15] indicated that healthy behavior is not only physical activity, but also a construct of mental, educational, and environmental situations that enables us to live a healthy life. In the situation of endometriosis and pain, or perception of pain, social factors and environment play an important role; thus, the social and psychological support might be of further relevance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding suggest that high levels of physical activity are associated with reduced risk of endometriosis. Regular physical exercise could be to improve levels of immune and anti-inflammatory markers and reduced menstrual flow that could lead to decreased endometriosis risk (8).On the other hand, in women with a higher level of exercise, increased levels of sex hormone-binding globulin (SHBG) can lead to reducing the level of bioavailable estrogen (8). Insulin resistance and hyperinsulinemia have been related to endometriosis risk that physical activity can reduce these.…”
Section: Discussionmentioning
confidence: 99%
“…Lifestyle factors play an important role in preventing many chronic diseases. Available evidence on the effect of lifestyle-related factors such as physical activity, nutritional status, body mass index, smoking, and SQ on endometriosis is controversial (1,(6)(7)(8)(9). Therefore, modified lifestyle recommendations in these patients have been discussed.…”
Section: Introductionmentioning
confidence: 99%